Gender and violence stereotypes couple covered in men and women from 18 to 24 years old - Quintana Peña, Alberto (2020)
This research aimed to determine the characteristics of gender stereotypes in the sample selected according to sex. Identify emerging beliefs regarding gender, relationships and violence; and finally to establish whether covert violence in couples, in men and women, presents significant differences. For this, the associative technique of natural semantic networks was used, adapted for the present work by the study group in order to estimate the degree to which each subject shares the stereotype of the group in relation to certain conceptualizations about women, relationships of couple and violence against women. On the other hand, the Covert Violence Scale was applied to measure the patterns of couple behavior. The results obtained show that both sexes have very particular characteristics in the stereotypes studied, describing the existence of beliefs different from the traditional ones in relation to gender, relationships and violence. Finally, no differences were found in covert violence according to sex.